2005
DOI: 10.1021/ic050324u
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and Electrochemical Properties of Heteroleptic Tris-Cyclometalated Iridium(III) Complexes

Abstract: Mixed (difluoro)phenylpyridine/(difluoro)phenylpyrazole tris-cyclometalated iridium complexes were prepared in order to study the effect of fluorination and the pyridine/pyrazole ratio on the emission and electrochemical properties. Increasing fluorination and replacement of pyridine by pyrazole both leads to a widening of the HOMO-LUMO gap and generally leads to a blue shift in emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
160
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(173 citation statements)
references
References 15 publications
(27 reference statements)
11
160
1
1
Order By: Relevance
“…In addition pyrazoles have been used for treatment of type 2 diabetes, obesity, thrombopiotinmimetics and antiangiogenesis because of their kinase inhibitory effects 20 . Furthermore, some pyrazoles are employed in polymer and supramolecular chemistry, in the food industry, and as UV stabilizers and cosmetic colorings and in some cases it was observed that these compounds also have liquid crystal properties [21][22][23][24][25] . Dihydropyrano [2,3-c]pyrazoles, are one of the most important pyrazole compounds and they have received considerable attention owing to their biological activity and they have been utilize as a template for medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In addition pyrazoles have been used for treatment of type 2 diabetes, obesity, thrombopiotinmimetics and antiangiogenesis because of their kinase inhibitory effects 20 . Furthermore, some pyrazoles are employed in polymer and supramolecular chemistry, in the food industry, and as UV stabilizers and cosmetic colorings and in some cases it was observed that these compounds also have liquid crystal properties [21][22][23][24][25] . Dihydropyrano [2,3-c]pyrazoles, are one of the most important pyrazole compounds and they have received considerable attention owing to their biological activity and they have been utilize as a template for medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Among all phosphorescent emitters under investigation, iridium (III) complexes are without contest among the most widely studied transition metal complexes: as neutral emitters [24] or as soft salts [25][26][27] for the design of OLEDs or as ionic complexes [28][29][30] for the design of Light-Emitting Electrochemical Cells (LECs). As main advantage over the other transition metal complexes, relatively short excited state lifetime enables to e ciently minimize the triplet-triplet (T-T) annihilation [31,32]. So far, metal complexes that are nearly non-emissive at room temperature but revealing a decent emission at 77K have only been scarcely in-vestigated as emitters for OLEDs [33].…”
Section: Introductionmentioning
confidence: 99%
“…Five member heterocyclic compounds such as pyrazole are important are important nitrogen containing compounds and numerous pyrazole derivatives have been found to possess considerable biological activities [6], such as antimicrobial [7][8][9], antiamoebic [10,11], antinociceptive [12], anticancer [13], antidepressant [14] and anti-inflammatory [15] . On the other hand, pyrazoline derivatives are also widely used in materials science fields such as non-linear optics (NLO) [16], optical limiting [17], electrochemical sensing [18], Langmuir films and photoinitiated polymerization [19]. On the other hand a pyrazole ring linked to five or six member heterocyclic systems with an azomethine group also showed a variety of biological activity such as antibacterial [20], anti-fungal [21], anti-inflammatory [22], antihypertensive [23], anti-HIV [24], antitumor [25], and anticonvulsant activities.…”
Section: Introductionmentioning
confidence: 99%